Digital Campaign #DiBengkuluAjo as Communication Strategy for Strengthening the Tourism Identity of Bengkulu Province - Rafinita Aditia; Lisa Adhrianti (Jurnal Komunikasi, 2025)
Tourism promotion in the digital era increasingly relies on social media as a fast, broad, and interactive means of communication. Bengkulu Province, with its potential for natural, cultural, and historical tourism, launched a digital campaign titled #DiBengkuluAjo to increase its appeal and strengthen its tourism identity. This study aims to analyze the campaign as a digital communication strategy in building Bengkulu's image as a tourist destination. The method used was a qualitative approach with a single instrumental case study design. Data were obtained through observation, in-depth interviews with the Bengkulu Provincial Tourism Office, and documentation of the campaign on social media, particularly Instagram. Data analysis was conducted using Nowak and Warneryd's communication campaign model, which includes eight main elements: expected effect, communication competition, communication object, target population, communication channel, message, communicator, and achieved effect. The results show that this campaign was effective in increasing public awareness of Bengkulu's tourism potential through engaging visual content, authentic narratives, as well as local community involvement and collaboration with content creators. The campaign's primary target audience was millennials and Gen Z, who are active on social media. The campaign's effectiveness is reflected in increased digital interaction, public participation, and contributions from the local creative economy sector. This campaign also fosters regional pride and strengthens Bengkulu's image as an attractive tourist destination. With an innovative and collaborative digital communication strategy, the #DiBengkuluAjo campaign has the potential to become a model for sustainable tourism promotion in the digital age.